A Young Girl with Brachymesophalangia V - Waseem Mehmood Nizamani; Farheen Raza (ziauddin University, 2024)
Brachymesophalangia is the most common hereditary anomaly of the middle phalanges. Brachymesophalangia-V (BMP-V) is the terminology used for a short and broad middle phalanx of the fifth digit which can present both alone and in a large number of complex brachydactylies with congenital disorders. Its frequency varied in different populations between 3.4% and 21%. To our knowledge no case of BMP-V has been reported from our country. We incidentally found a case of BMP-V who presented to us with the history of trauma which is presented in this case report. Literature search showed that this condition is caused by heterozygous mutations in the Indian hedgehog (IHH) gene. Key Words: Brachydactyly; BMP-V; Phenotype; Skeletal Dysplasia; Hand.